MANAJEMEN STRATEGIS DIGITALISASI BANK: BPRS PEMERINTAH DAERAH DI INDONESIA - Syaifuddin Syaifuddin; Abu Sanmas; Asep Hedi Turmudi (Asy Syar'iyyah: Jurnal Ilmu Syariah dan Perbankan Islam, 2023)
This study aims to describe and map the strategic management of BPRS belonging to the regional government in North Maluku Province in entering the banking industry era 4.0. Documenting and analyzing the achievements of micro Islamic banks in North Maluku Province entering the digitalization of Islamic banking. This research succeeded in identifying the resources based view and the challenges opportunities of each BPRS. By using strategic management analysis and SWOT (Strength, Weaknessen, Opportunity, and Threat) analysis, the government-owned BPRS is ready to enter the era of digital banking. The two regional government-owned sharia banks have representative facilities, ATMs, digital payment systems, mobile payment applications, competent human resources, extensive service networks on several islands, development of information technology facilities and human resources that are continuously upgraded.